Linaceae endémicas del Perú - León, Blanca (2006)
The Linaceae are represented in Peru by three genera and eight species (Brako & Zarucchi, 1993; Ulloa Ulloa et al. 2004), all herbs. One species in the genus Linum is recognized as endemic. This species grows in the Desert Shrubland, Mesoandean, and Humid and Dry Puna regions, between 1740 and 3100 m elevation. It has not been recorded in the Peruvian protected areas system.